VARIASI AKTIVITAS HARIAN Hylobates moloch (Audebert, 1798) MENURUT KELAS UMUR DI TN GUNUNG HALIMUN, JAWA BARAT - Kartono, Agus P; Prastyono, Prastyono; Maryanto, Ibnu (BERITA BIOLOGI, 2002)
The study of daily activity of (Hylobates moloch Audebert 1798) was conducted in Cikaniki. Ciawitali and Pasir Bivak TN Gunung Halimun for two months from June to July 1999.Commontly the daily activity for Jawan Gibbon are resting 39.1%, feeding 30.3%, moving 24.1% and other social activity 6.5% in average.Based on the meaning of activity category, the most for feeding;activity used by subadult (45%), moving for juvenile (33%), resting for infant (82%) and social for juvenile (15.72%).The least social activity was done by subadult category (0.4%). The space area for Jawan Gibbon activity was done at 5-15 meter (23%), 16-25 meter (43%), 26-35 meter (30%) and upper or top canopy at 35 meter from ground (4%).On this study also indicated that this gibbon turn down until to 1.5 meter from ground at lepus (Ammonium pseudopoetens) vegetation.